Menimbang Pentingnya Desentralisasi Partai Politik di Indonesia - Ahmad Solikhin (Journal of Governance, 2017)
The role of political parties in Indonesia after the reform era is to become the main actor of democracy in mobilizing the political life of the nation and state. Unfortunately, the democratization process does not work well in the body of the political party itself. Political parties tend to be antithetical to democracy in government politics. Political decentralization and the authority of political parties are the most important elements in evaluating the working system of political parties. To date, the dynamics of party-party at the local level are still strongly dominated by the center. As a result politics in the region is a political derivation in Jakarta. Stakeholder party with decentralized authority will not create a democracy at the local level in political parties, because the party's internal democratic practices are highly centralized, clientelistic and oligarchic. The challenge must beanswered if it wants to create a democracy within the internal political party. Particularly related to efforts to build decentralization of political party authority in determining candidate process in elections. By viewing the party as an organization of public legal entity which is one of the instruments of democracy, the political party should have started democratizing internally if it is not desirable to be abandoned by society and has the goal of improving Indonesian democracy.